Treatment of Mucous Cyst of the Distal Interphalangeal Joint With Osteophyte Excision and Joint Debridement - Fan, Zhiyi; Chang, Li; Su, Xing; Yang, Binbin; Zhu, Zhe (Frontiers in Surgery, 2022)
Background: Mucous cyst of the distal interphalangeal joint (DMC) or interphalangeal connection of thumb is common in middle-aged and elderly people, and it often occurs in the fingers of osteoarthritis (OA). Although there are many conservative treatments, DMC is usually treated by surgery. The common complications of surgical treatment are recurrence of DMC and skin necrosis. This article introduces the method and clinical effect of osteophyte excision and joint debridement in the treatment of DMC of distal interphalangeal joint. Methods: Eighteen cases of affected fingers made an'S 'incision in the distal interphalangeal（DIP）joint under local anesthesia to remove the osteophyte of the distal interphalangeal joint, clean the dorsal joint capsule, wash the joint, and retain only the bilateral collateral ligament and extensor tendon device. It is suspected that the injured finger of extensor tendon should be protected by external fixation. Results: In 15 cases, except for 1 case with partial skin necrosis and healed after dressing change, the incisions healed well in all the 15 cases. The visual analog scale（VAS ) scores of all affected fingers after operation were higher than those before operation (VAS score: 4.93±0.88 vs. 4.07±1.03, P < 0.05).The range of motion（ROM） of the affected finger decreased in 1 case, and the postoperative activity of the other fingers increased in varying degrees (ROM：67.60±5.40 vs71.27±7.06, P > 0.05). Conclusions: Using osteophyte excision and joint debridement to treat DMC can avoid skin necrosis caused by cyst removal and can avoid the recurrence of DMC to the greatest extent, so it is a safe and effective way of treatment.